Dissemination of Waves in Thin Plates - Klimenda, František; Rychlíková, Lenka; Husár, Štefan; Soukup, Josef (Manufacturing Technology Journal, 2017)
The article deals with the wave propagation in thin plate. A wave was caused by the impact force. In the first part of an article the Kirchhoff's theory of thin isotropic plate is given. It is a vertical displacement w, angles of rotation tangent φx and φy, bending stresses σx, σy, shear strength τyx = τyx, shear strength from displacement forces τxz, τyz. In the second part of an article is solved a Kirchhoff's theory by analytically in MATLAB programme. Analytically were solved only displacements u, v and velocity u ̇,v̇ . The solution is performed for two plate materials - aluminium and steel. By result are deformations and velocities graphs in the x-axis and the y-axis at the measurements points given. In the conclusion of an article is comparing of individual deformations and velocities graphs.
Keywords: Displacement; Velocity; Vibration; Thin Plate